Carbon in Diesel Particulate Matter: Structure, Microwave Absorption and Oxidation - V. S. Babu; L. Farinash; M. S. Seehra (The National Institute for Occupational Safety and Health (NIOSH), 1996)
"The diesel particulate matter (DPM), a constituent of the diesel engine exhausts, is known to be a potential carcinogen. 1- 3 Consequently, suitable methods to control/eliminate DPM have ·been under investigation in recent years. The DPM can be controlled by using fibrous ceramic traps. However, clogging of traps by DPM requires the impractical periodic trap replacement. Following the recent work by Garner and Dent,4,5 we are investigating the in situ use of microwaves to regenerate the ceramic traps, thereby eliminating the trap replacement step in this process. The use of microwaves instead of conventional heating for trap regeneration has the advantage of selective heating of the DPM instead of the trap, if the trap absorbs insignificant microwave power relative to the DPM. Also, the oxidation characteristics of the DPM are needed to understand fully this regeneration process.The rate of energy absorption P per unit volume of a sample is given byP = wE"" |Eo|2 • (1 )where w is the angular frequency, |E0|2 is the intensity of the microwave radiation, and E” is the imaginary part of the dielectric constant (E = E’ + iE”) . Thus measurements of E11 for DPM and ceramic trap material are needed to determine their capacities for microwave absorption. In this paper, we report these measurements carried out at · a frequency of 8.7 GHz. Following microwave absorption, the DPM is expected to oxidize. The oxidation characteristics of the DPM have been investigated using Fourier transform infrared (FTIR) spectroscopy of the evolved gases CO2 and CO and using thermogravimetric analysis (TGA). Finally, some information on the structure of carbon in DPM has emerged from the analysis of its x-ray diffraction spectra. Results of these experiments are reported in the following pages."